Effect of diet and packaging system on the oxidative status and polyunsaturated fatty acid content of rabbit meat during retail display. (September 2018) - Dal Bosco, Alessandro; Mattioli, Simona; Cullere, Marco; Szendrő, Zsolt; Gerencsér, Zsolt; Matics, Zsolt; Castellini, Cesare; Szin, Melinda; Dalle Zotte, Antonella
Abstract: The aim of this study was to evaluate the combined effect of two dietary lipid sources (sunflower vs. linseed oil) and three packaging methods (PVC film – BAG vs. modified atmosphere CO2 20% + 80% O2 – MAP vs. and vacuum - VAC) on the oxidative status and polyunsaturated fatty acid content of rabbit loins ( Longissimus thoracis et lumborum muscle), at days 1, 4 and 10 of simulated retail display. The diet, storage time and packaging method affected the oxidative status of rabbit meat under retail display. As expected, storage time, independently on the other factors, significantly reduced the antioxidant content of loin meat. Accordingly, TBARs values significantly increased during storage, as well as the dietary supplementation of linseed. The fatty acid profile of the fresh loin closely respected that of the diets. At day 10, oxidative status and fatty acid profile of MAP samples could be yet considered optimal. Highlights: The effect of dietary linseed and packaging on oxidative status of rabbit meat was studied. A ten days long shelf-life trial under chilled conditions was planned. 3% linseed oil in rabbit diet affected the fatty acids profile of meat. Oxidation increased during storage independently to treatment. MAP packaging was the most effective method for shelf-life increase.